Plastic responses to temporal variation in moisture availability: consequences for water use efficiency and plant performance - Picotte, Joshua J; Rosenthal, David M; Rhode, Jennifer M; Cruzan, Mitchell B (Oecologia, 2007)
The ability to appropriately modify physiological and morphological traits in response to temporal variation should increase fitness. We used recombinant hybrid plants generated by crossing taxa in the Piriqueta caroliniana complex to assess the effects of individual leaf traits and trait plasticities on growth in a temporally variable environment. Recombinant hybrids were used to provide a wide range of trait expression and to allow an assessment of the independent effects of individual traits across a range of genetic backgrounds. Hybrid genotypes were replicated through vegetative propagation and planted in common gardens at Archbold Biological Station in Venus, Florida, where they were monitored for growth, leaf morphological characters, and integrated water use efficiency (WUE) (C isotope ratio; δ¹³C) for two successive seasons. Under wet conditions only leaf area had significant effects on plant growth, but as conditions became drier, growth rates were greatest in plants with narrow leaves and higher trichome densities. Plants with higher WUE exhibited increased growth during the dry season but not during the wet season. WUE during the dry season was increased for plants with smaller, narrower leaves that had higher trichome densities and increased reflectance. Examination of alternative path models revealed that during the dry season leaf traits had significant effects on plant growth only through their direct effects on WUE, as estimated from δ¹³C. Over the entire growing season, plants with a greater ability to produce smaller and narrower leaves with higher trichome densities in response to reduced water availability had the greatest growth rate. These findings suggest that plants making appropriate changes to leaf morphology as conditions became dry had increased WUE, and that the ability to adjust leaf phenotypes in response to environmental variation is a mechanism by which plants increase fitness.